Viral entry into host cells - Simmons, Graham; Pohlmann, Stefan (Advances in Experimental Medicine and Biology, 2013)
For a virus to invade a host cell it needs to penetrate the physical barrier imposed by the plasma membrane. Viruses have evolved specialized surface proteins to meet this challenge. These proteins facilitate delivery of the viral genetic information into the host cell by either fusing the viral envelope with a host cell membrane or by forming membrane pores. Membrane fusion and pore formation critically depend on the engagement of host cell receptors and receptor choice is a key determinant of viral tropism. The multi-faceted interplay between viral and cellular factors during virus entry is a fascinating field of study, which can provide important insight into viral pathogenesis and define new targets for intervention. This book provides a comprehensive overview of this exciting field of research.